EFEKTIVITAS PROGRAM MUSYAWARAH PERENCANAAN PEMBANGUNAN KECAMATAN (MUSRENBANGKEC) DALAM PENYUSUNAN RENCANA KERJA PEMERINTAH DAERAH (RKPD) KABUPATEN SUMEDANG TAHUN 2023 - Akadun; Hendrayana, Erlangga Putra Pamungkas; Ellwansa, Villsa; Pratiwi, Listy Chairul Nisa Indah; Anggraeni, Nenden Vera Devi; Virgyawan, Muhammad; Maulana, Rohmat Hidayat (JRPA - Journal of Regional Public Administration, 2025)
This research aims to determine the effectiveness of the Program Musyawarah Perencanaan Pembangunan Kecamatan (MusrenbangKec) for preparation of Rencana Kerja Pemerintah Daerah (RKPD) Kabupaten Sumedang Tahun 2023. The research method used in this research is a qualitative research method. The informants in this research were Staf Bidang Perencanaan, Pengendalian, dan Evaluasi Pembangunan Daerah, Kasubag Program dan Keuangan Kecamatan Sumedang Selatan, and Forum Delegasi Musrenbang Kota Kulon. The data collection techniques used were literature study and field study consisting of observation, interviews and documentation. The data validity techniques used are creativity, transferability, dependability and confirmability tests. Meanwhile, the data analysis techniques in this research are data reduction, data presentation, verification and data triangulation. Based on the research results, it was concluded that the effectiveness of the effectiveness Program Musrenbang Kecamatan in preparation RKPD Kabupaten Sumedang Tahun 2023 this can be seen from the consistency andharmony of program content, suitability of program implementation with implementation mechanisms, as well as the goals and objectives, impact of implementation, output policies, outcome policies and benefit policies in implementing the program Musrenbang Kecamatan include the need for better coordination between regional and sub-district governments in allocating budgets, the need for better understanding of all stakeholders in planning development plans, and the need to be able to prioritize development proposals that truly constitute a development urgency